Child in conservative renal treatment: maternal interactions with the social support network - Fernanda Lise; Eda Schwartz; Viviane Marten Milbrath; Bianca Pozza dos Santos; Eliana Buss; Rita Maria Heck (Universidade Estadual de Maringá, 2018)
This study aimed to know the interaction of the mother of the child in renal conservative treatment with the social support network. Qualitative delineation, whose theoretical reference was Symbolic Interactionism. For data collection, we used semi-structured interview, genogram and ecomap. Eleven mothers of children undergoing conservative renal treatment participated. The data were analyzed with conventional content analysis. It was possible to construct two categories: Being supported by the formal social support network; Being supported by the informal social support network. The analysis showed that the main source of maternal support was related to the family. In addition, the mothers stressed the importance of the support of professionals, health services and non-governmental organization. It is concluded that Nursing can improve the targeting of care actions aimed at the family of the child in renal conservative treatment, expanding the social support network.